Analysis of motivation factors: Dependance on personal and professional characteristics of employees - Marija Rakić; Marija Radosavljević; Vesna Janković Milić (Economic Themes, 2022)
Organizations invest in different types of resources, which enable them to achieve and maintain their market position and remain competitive. With global competition and changing market environment, one of the key resources, which considerably contributes to improvement of organizations' competitive posture, are human resources, i.e. employees. The subject of research presented in this paper are factors of employees' motivation. The aim of the research is to determine the impact of certain factors on employee motivation, based on the importance that different motivation factors have, depending on certain personal and professional characteristics of employees. Based on the results of the survey, the most important factors of motivation are financial factors, specifically the 'salary' and 'financial rewards', as well as 'job security' as non-financial factor. The variance of repeated measurements showed that there is statistically significant influence of financial motivation factors on employee motivation. However, the results of the analysis of the variance indicate that it is necessary to find the appropriate combination of financial and non-financial motivators, having in mind different characteristics and needs of employees, in order for the employee motivation system to show the expected results.
Keywords: J53; M52; M54; 330; motivation; financial factors; non-financial factors; employees; personal characteristics; professional characteristics